Spatial analysis of ethnopolitical mobilisation in the Caucasus in the 1980s and 1990s - Jelen Libor (Bulletin of Geography. Socio-Economic Series)
The paper aims to create a set of indicators which could best explain the varying intensity of ethnopolitical mobilisation in the Caucasian region. Selected data on social indicators of individual Caucasian territorial units are examined with help of correlation and regression analysis. The analysis results also show relations among individual social indicators which can help understand social and ethnic processes within the units.